The Endowments of Tahir Musa al-‘Arabi in the Cities of Nablus and Jenin and Their Environs Ramadan 1256 AH / October 1840 AD - AL-Hizmawi, Muhammad Majid (Jordan Journal for History and Archaeology, 2024)
This study investigates the endowment of Tahir Musa al-‘Arabi in the cities of Nablus and Jenin and their environs that was registerd in the Nablus Sharia Court in Ramadan 1256 AH/ October 1840 AD. The article is divided into four topics. The first topic is a presentation of the life of the endower. The second topic is an examination of the text of the endowment and the conditions that must be met by the endowment. The third topic is an analysis of endowed real estate. The fourth topic is discussion of the conditions set by the endower for his endowment. The researcher follows four approaches; the inductive and historical approaches, which depend on the extrapolation and analysis of the endowment text. The article also relies on the statistical quantitative approach by collecting numerical data and presenting it in tables. The researcher also uses the comparative approach by comparing the endowed real estate and the real estate acquired by the endower that is registered in the records of the Sharia court. The study reached several results: the endowment document and the information it contains is one of the first sources of the historical documentation. It is also a witness to the history of Nablus city that reflects a realistic picture of the public life of the Nabulsi community during the period under study. Family endowments maintain continuity of real estate ownership and contribute to the economic and social development of society.